1984
DOI: 10.1055/s-2008-1036707
|View full text |Cite
|
Sign up to set email alerts
|

Die Beeinflußbarkeit der Samenqualität durch Akupunktur bei subfertilen Männern

Abstract: Our first attempt in treating subfertility by acupuncture was carried out on 28 males. The results obtained from the experiences in veterinary medicine encouraged us to attempt this type of therapy. Each patient received a total of 10 treatments for a period of three weeks. Several spermiograms were made after diagnosis subfertility. We checked spermiograms and hormone levels before and after acupuncture. Total count, concentration and motility were evaluated. In all cases we observed a statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Indeed, there are reports that approximately one-fifth of the males involved in fertility investigations consult fringe medicine, including acupuncture [ 1 51. Acupuncture, the ancient Chinese art of healing, is claimed to have a beneficial effect on some pathological conditions, including impaired sperm quality [6][7][8][9]12, 171. However, data on the possible positive effect of acupuncture treatment on semen parameters are largely uncontrolled and are mainly limited to sperm density and motility [6, 7, 9, 12, 171.…”
Section: S Siterman Et Almentioning
confidence: 99%
“…Indeed, there are reports that approximately one-fifth of the males involved in fertility investigations consult fringe medicine, including acupuncture [ 1 51. Acupuncture, the ancient Chinese art of healing, is claimed to have a beneficial effect on some pathological conditions, including impaired sperm quality [6][7][8][9]12, 171. However, data on the possible positive effect of acupuncture treatment on semen parameters are largely uncontrolled and are mainly limited to sperm density and motility [6, 7, 9, 12, 171.…”
Section: S Siterman Et Almentioning
confidence: 99%
“…Thus, the improved basal cell proliferation in the present study may be partly mediated via EA-induced upregulation of FSH. Accumulating evidence suggest that acupuncture restored the lowered FSH to normal level in subfertile men 23 . However, whether EA played a similar role in the present study on regulation of FSH needs further investigations.…”
Section: Discussionmentioning
confidence: 51%
“…It was reported that heat treatment did not affect plasma and testicular testosterone concentrations, 25 although an increased in serum LH may drive the Leydig cells to produce enough testosterone to maintain normal spermatogenesis 48 , 49 . In line with this, both acupuncture and Chinese herbs were found to restore the reduced LH and testosterone concentrations in subfertile men and rats 23 , 50 …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The first published study on treatment of infertility by needle acupuncture was in 1984 by a German research group, inspired by its promising use in veterinary medicine. Fischl et al [41] compiled a case study of 28 subfertile males. Each patient received a total of 10 acupuncture treatments over three weeks.…”
Section: Infertilitymentioning
confidence: 99%